The use of antihypertensive drugs in the treatment of essential hypertension at outpatient installations, Puskesmas Karang Rejo, Tarakan - Salma Nara Fadhilla; Dharma Permana (Yarsi Journal of Pharmacology, 2020)
Background: Essential hypertension is the most common type of hypertension, affecting 95% of hypertensive patients. Essential hypertension can be managed through a combination lifestyle changes and antihypertensive drugs. The aim of this study was to know the use of antihypertensive drugs in the treatment of essential hypertensive at outpatient installations, Puskesmas Karang Rejo, Tarakan.Methods: The research method is descriptive by using secondary data from complete patient medical records of the essential hypertension patients undergoing outpatient treatment at Puskesmas Karang Rejo, Tarakan in the period of January-April 2017.Results: A total of 557 medical records were selected, there were 72.53% (n = 404) female and 27.47 % (n = 153) male; age ranged from 20-80 years (mean = 50.32 years). The most common of essensial hypertension were 47.22 % (n = 263) grade II hypertension and 45.42 % (n = 253) grade I hypertension. The antihypertensive drugs were used single or in combination in the following order: Amlodipine (Calcium channel blockers), Captopril (ACE inhibitors), Hydrochlorothiazide/HCT (Diuretic), Methyldopa (alpha-2 adrenergic receptor agonist) and Isosorbid dinitrate (Vasodilator). Four hundred fifty four (81.51%) patients were treated with a single drug (monotherapy) and 103 (18.49%) patients were given combination therapy. Monotherapy and the combination of two antihypertensive drugs were used for prehypertension, grade I hypertension and grade II hypertension, with the most widely used drugs as monotherapy was amlodipine (67.86%, n =378 ) and the mostly used combination therapy of two antihypertensive drugs was Amlodipine-Hydrochlorothiazide (15.80%, n = 88).  The combination of antihypertensive Amlodipin-Hydrochlorothiazide-Captopril (0.35%, n=2) was used for hypertension grade II.Conclusion: Amlodipine was the most widely used drug as monotherapy or combination drugs therapy in the treatment of essensial hypertension at outpatient installations, Puskesmas Karang Rejo.